IMMU-48. CD4+ T CELLS RESTRICT MEDULLOBLASTOMA GROWTH AND DISSEMINATION. (9th November 2020) - Eisemann, Tanja; Wechsler-Reya, Robert
Abstract: The immune system serves as a powerful defense not only against pathogens and parasites but also against neoplastic cells. Emerging immunotherapies that boost the activity of tumor-reactive immune cells or counteract immune suppressive mechanisms have shown promising effects in certain types of cancer. However, the success of immunotherapy for brain tumors has been limited, highlighting the need for a better understanding of the immune microenvironment in these tumors. Our previous studies have shown that T cells critically affect growth of the pediatric brain tumor medulloblastoma. In particular, depletion of CD4+ T cells results in more aggressive growth of medulloblastoma cells and allows these cells to metastasize to the spinal cord. The anti-tumoral effects of CD4+ T cells are not due to their function as helpers for CD8+ cytotoxic T cells, since CD8+ T cell depletion did not enhance tumor growth to the same extent as CD4+ T cell depletion. To test whether CD4+ T cells can recognize MHC class II molecules on tumor cells and attack these cells directly, we generated tumors from MHC class II knockout mice. Surprisingly, depletion of CD4+ cells in these animals still enhanced tumor growth and metastasis. These results suggest that CD4+ T cells regulate medulloblastoma growth and metastasis in a manner that is independent of CD8+ T cells and independent of MHC-II on tumor cells. Ongoing studies are aimed at elucidating the mechanisms by which CD4+ T cells regulate medulloblastoma growth, including the antigen-presenting cells that activate them and the effector cells responsible for killing tumor cells following their activation. These studies will advance our understanding of the immune microenvironment in medulloblastoma and allow us to design more effective therapies for controlling tumor growth and metastasis.